Mobility Should Be Fun. A Consumer (Law) Perspective on Border Check Technology - Paul De Hert; Rocco Bellanova (The Scientific World Journal)
After 9/11, states looked at transportation as if it was a matter of paying taxes: “We cannot make it fun, but we can make it efficient.” When traveling, we are asked to pass on data, give body samples, and pass through body scanners in the name of the general interest and in the name of our safety. Technology complements existing human checks and controls. Here we take a fresh look at the new security apparatuses and make transportation of humans more passenger-centered. Consumer protection law might help to complement the existing use of data protection law principles by citizen organizations. It should be possible to satisfy consumer needs, without forgetting the perspective of the citizen.